2020
DOI: 10.1098/rstb.2019.0347
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements as a potent source of diverse cis -regulatory sequences in mammalian genomes

Abstract: Eukaryotic gene regulation is mediated by cis -regulatory elements, which are embedded within the vast non-coding genomic space and recognized by the transcription factors in a sequence- and context-dependent manner. A large proportion of eukaryotic genomes, including at least half of the human genome, are composed of transposable elements (TEs), which in their ancestral form carried their own cis -regulatory sequences able to exploit the host trans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(176 citation statements)
references
References 108 publications
(157 reference statements)
6
153
0
Order By: Relevance
“…Previous reports have shown that orphan genes generally have lower expression levels but higher tissue-specific expression compared to phylogenetically conserved genes (Levine et al , 2006; Donoghue et al , 2011; Wu, Irwin and Zhang, 2011). Several hypotheses have been proposed to explain the regulation of these younger genes that lead to tissue-specific and/or stage-specific expression, including transposon insertion upstream of the transcription start-site, shared regulatory elements with older genes (possibly by gene overlap), association with a bidirectional promoter, or by being located within an intron (Maksakova and Mager, 2005; Toll-Riera et al , 2008; Arendsee, Li and Wurtele, 2014; Sundaram and Wysocka, 2020). We explored the cis-regulatory elements in the putative promoter regions of these genes below.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that orphan genes generally have lower expression levels but higher tissue-specific expression compared to phylogenetically conserved genes (Levine et al , 2006; Donoghue et al , 2011; Wu, Irwin and Zhang, 2011). Several hypotheses have been proposed to explain the regulation of these younger genes that lead to tissue-specific and/or stage-specific expression, including transposon insertion upstream of the transcription start-site, shared regulatory elements with older genes (possibly by gene overlap), association with a bidirectional promoter, or by being located within an intron (Maksakova and Mager, 2005; Toll-Riera et al , 2008; Arendsee, Li and Wurtele, 2014; Sundaram and Wysocka, 2020). We explored the cis-regulatory elements in the putative promoter regions of these genes below.…”
Section: Resultsmentioning
confidence: 99%
“…These studies supported the longstanding hypothesis that TE domestication is important in eukaryotic genome evolution and that some TEs play integral roles in regulating gene expression. However, most of these studies were focused on Class I TEs in animal and human systems (Sundaram and Wysocka, 2020). In this study, we identified a new mechanism by whichClass II TEs can influence gene regulation in maize.…”
Section: Discussionmentioning
confidence: 93%
“…Transposable elements (TEs) have been shown to influence gene regulation via participation in genome folding and generation of regulatory elements, with expansions of TEs influencing evolution of gene expression across species (Sundaram and Wysocka, 2020) . Specific TEs have previously been shown to be enriched within LADs, and LADs are postulated to be a key element in multiple mechanisms that many species have evolved to silence and limit accessibility to highly repetitive DNA and other TEs (Hollister and Gaut, 2009;Meuleman et al, 2013) .…”
Section: T1-and T2-lads Have Distinct Genomic Featuresmentioning
confidence: 99%